FORMATIVE RESEARCH PROGRAM AND ITS EFFECT ON THE INVESTIGATIVE COMPETENCES OF STUDENTS OF THE NURSING FACULTY OF THE NATIONAL UNIVERSITY OF HUANCAVELICA - Bollet Ramírez, Frank (2020)
The study sought to verify the effect of aformative research program on investigative skillsin Nursing students at the National University ofHuancavelica. The research was applied witha pre-experimental design. Questionnaires andobservation cards were administered to a sampleof 62 students from the first cycle "A" and "B",using the simple random sampling technique. Theresults obtained in the investigative skills in the pretest indicate that 9% of the students carry out thebibliographic search, 12% use technological means,7% apply methodology, 4% apply the communicationof results and 45% apply the practice of values. Aftercompleting the formative research, the investigativeskills measured in the post test indicate that 33% ofthe students carry out a bibliography search, 61%use technological means, 35% apply methodology,39% apply the communication of results and 11%apply the practice of values. In conclusion, formativeresearch significantly influences research skills.